Design and Performance Analysis of a Cooling Tower in Sulfuric Acid Plant - Chowdhury, BA; Islam, MS; Begum, F; Parvez, AM (Journal of Chemical Engineering, 2010)
Journal of Chemical Engineering Vol.ChE 23 1995-2005